Sexual Intimacy, Mental Illness, and Homelessness. Issue 1 (15th December 2017) - Ecker, John; Cherner, Rebecca; Rae, Jennifer; Czechowski, Konrad
Abstract: The current article reviews the literature on sexuality among individuals with a severe mental illness (SMI) who have experienced homelessness, a topic that has received little attention in the research literature, particularly from a community psychology perspective. The review begins with a synthesis of the literature on SMI and sexuality, followed by a review of the available literature on SMI, homelessness, and sexuality. It concludes with an interpretation of the findings using community psychology values and principles. The findings highlight the importance of intimate relationships to recovery for many individuals with an SMI who have experienced homelessness. Policy implications for homeless shelters and housing interventions are discussed. Highlights: Sexual intimacy is critical to well‐being, but rarely examined within the context of homelessness. Intimacy is valued by individuals with serious mental illness who experience homelessness. Barriers to intimate relations include isolation, housing concerns, and institutional restrictions. Community psychology principles can help individuals foster intimate relationships. Individuals with lived experience should guide policy development within homeless serving agencies.